ABOUT NECESSITY OF DEVELOPMENT OF ADVANCED METHODS FOR ASSESSMENT OF MATERIALS POROSITY - A. Anisovich; A. Buinitskaya (Литьë и металлургия)
The paper discusses determination of materials porosity by the method of comparison defined in the standard GOST 9391–80 «Hard sintered alloys. Methods used for porosity and microstructure determination». The necessity and possibility of porosity assessment by the method of computer planimetry are shown. Using GOST 9391 standard scales the porosity was determined by means of the «Image SP» program for processing of images. It is shown that the error of determining the porosity is associated with a low quality of graphic material which also makes difficult determination of porosity by the method of comparison.